Pelatihan POM-QM for Windows Dalam Penyelesaian Permasalahan Transportasi Bagi Mahasiswa - Anugrah Ilahi, Andi Alfianto (Lembaga Penelitian dan Pengbdian Masyarakat (LP2M) Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
Transportation is an activity to move a product from the origin to the destination location where the implementation of inappropriate transportation will make transportation costs expensive which has an impact on the high price of goods or services offered to the public. The transportation method is a tool used to determine the right delivery allocation to get optimal transportation costs. Where the methods used in transportation methods to obtain optimal transportation costs include: 1) North West Corner (NW); 2) Least Cost and 3) Vogel Approximation Method (VAM) and the next step of the three methods is using the Stepping Stone. These steps have been studied by students in lectures, it's just that the calculations using the transportation method are still done manually so that complex transportation problems will be difficult to do and take a long time. Therefore, the POM QM for Windows training given to students is able to provide skills to students to be able to solve complex transportation problems quickly and accurately. From the training provided, it is known that the use of POM QM for Windows provides benefits for students and students are able to use the POM QM application for Windows after the training.